Problem-Based Learning Students' Perceptions of Knowledge and Professional Identity: Occupational Therapists as 'Knowers'. (January 2013) - Whitcombe, Steven W
Purpose: The future of occupational therapy is dependent on profession-specific knowledge to underpin its practice. This research explored occupational therapy students' perceptions of knowledge and their professional identity from one problem-based learning programme. Procedure: A qualitative methodology using in-depth interviews gathered data from 20 occupational therapy students in their final year of an undergraduate programme. The data were analysed thematically and in relation to theoretical constructs derived from the sociologists of education, Basil Bernstein and Karl Maton. Findings: The students viewed occupational therapists as 'knowers' rather than as 'knowledgeable' therapists. This distinction is embedded in a professional identity grounded in the dispositions of the occupational therapist and the philosophical constructs that support occupational therapy, but not in the specialist knowledge of occupation. Conclusion: The students' experiences suggest that the problem-based learning programme provides the transferable skills and philosophical constructs that allow them to practise in a diverse range of contemporary occupational therapy settings. However, simply mirroring current practice restricts professional advancement. The identity of the occupational therapist needs to embrace both a philosophical discourse and the specialist knowledge of occupation.